INTEGRATED FOOD THERAPY PRODUCT FORMULA DARI PEKTIN KULIT PISANG AGUNG SEMERU (Musa paradisiaca Formatypica), MANGGA DAN DAUN MINT SEBAGAI ANTI-KONSTIPASI PADA TIKUS WISTAR - Nike Nurlaily Fitria; Rofiqoh Fajarwati; Tri Dewanti Widyaningsih (JURNAL AGROTEKNOLOGI, 2017)
This research aimed to optimize the formula of effervescent powder from banana peel pectin, mango, mint and to know the effect of effervescent powder to the reduction of constipations symptom of Wistar rats. This research used Response Surface Methodology (RSM) with Central Composite experimental Design (CCD) to optimize the formula of effervescent powder and used Complete Randomized Design (CRD) method with consumption of effervescent powder treatment factor for five days. The result of this research showed that the formula of effervescent powder which had high dietary fiber degree is in the proportion of pectin powder:mango powder:mint leaves powder respectively 40%:35%:25% with verified dietary fiber degree is 30.35%. Then, in anti-constipation test shows that effervescent powder feeding with dosage 180 mg/200 g BB had real effect (α=0.05) to all parameters but it didn’t influence the number of feces. Keywords: effervescent, constipation, pectin